Verdi - Cannon, Janell, 1957-; Dauer, Herminia (Barcelona : Juventud, 1997)
A young python does not want to grow slow and boring like the older snakes he sees in the tropical jungle where he lives.
Translation of: Verdi.
Keywords: Pythons -- Fiction; Snakes -- Fiction; Old age -- Fiction